A brief research study on novel antibiotic producing isolate from VIT Lake, Vellore, Tamil Nadu - Prithwijit Sarkar, Shreya Bhagavatula, Suneetha V (Journal of Applied Pharmaceutical Science, 2014)
The soil ecosystem has an enormous amount of microorganisms, and some of these microorganisms can potentially be useful to us. Bacillus and Actinomycetes are the most abundant microorganisms present in soil and both are known to produce antibiotics and inhibit the growth of other microorganisms. However, there are other potential microorganisms which may have such beneficial properties and are unknown to us. In this study, various microorganisms in the soil were screened to isolate an antibiotic producing microorganism. Soil was collected from VIT lake and serially diluted followed by crowded plate technique to screen for antibiotic producing colonies. The colony which was suspected to produce antibiotics was selected and sub-cultured by streaking. Antibiotic-sensitivity test was performed on Mueller-Hinton Agar and the inhibitory effect of the isolated microorganism towards the growth of bacteria was observed. The growth curve of the isolated microorganism was found out. Characterization was done by performing various biochemical tests and staining methods. Antibiotic production media was prepared, and the antibiotic production of the microorganism was plotted against time. From the antibiotic production curve, it was found that the 6th day showed the maximum antibiotic productivity.
Keywords: Soil, Anti-microbial activity, Crowded-plate, Antibiotic Sensitivity Test, Zone of inhibition.